Conservative Management of an Advanced Abdominal Pregnancy at 22 Weeks - Louis Marcellin; Sophie Ménard; Marie-Charlotte Lamau; Alexandre Mignon; Marie Stephanie Aubelle; Gilles Grangé; François Goffinet (Thieme Medical Publishers, Inc., 2014)
Abstract Objective We report an uneventful conservative approach of an advanced abdominal pregnancy discovered at 22 weeks of gestation. Study Design This study is a case report. Results Attempting to extend gestation of an advanced abdominal pregnancy is not a common strategy and is widely questioned. According to the couple's request, the management consisted in continuous hospitalization, regular ultrasound scan, and antenatal corticosteroids. While the woman remained asymptomatic, surgery was planned at 32 weeks, leading to the birth of a preterm child without any long-term complications. Placenta was left in situ with a prophylactic embolization, and its resorption was monitored. Conclusion Depending on multidisciplinary cares and agreement of the parents, when late discovered, prolonging advanced abdominal pregnancy appears to be a reasonable option.